Urban Planning in Remote, Extreme Environments ... - Hudgins, Ethan (Columbia University, 2019)
Remote, extreme settlements often depend on an equally extreme dedication of resources and planning to achieve their goals, whether geopolitical, scientific, extractive or otherwise. This thesis uncovered pitfalls of these settlements, adding to the existing literature through a critical analysis of McMurdo Station, Antarctica. McMurdo exists as the logistical hub for the U.S. Antarctic Program, supporting the science activities on the continent. The remoteness and severity of the environment, combined with the numerous, well-documented failures of planning, have resulted in an operationally inefficient and substantially improvable station. This study adopts a mixed methods approach unique among planning methodologies, incorporating interviews of involved planners, scientists, and analysts, available planning documents and literature, and a Building Information Model (BIM) to qualitatively and empirically analyze the station planning and resulting design. This study found that remote, extreme settlements ...